Analisis Permintaan Jasa Transportasi Funotrans Di Kota Bandar Lampung - Karina Mutiara Hati Sesunan; Arivina Ratih (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
This study aims to determine and analyze respondents' income variables, prices for FunoTrans services, prices for other services, and user satisfaction with the number of requests for FunoTrans transportation services in Bandar Lampung City. The research uses descriptive quantitative methods which are classified as survey research, namely research that takes samples from one population by using a questionnaire. The research method uses multiple linear regression analysis. The results of this study include; the price of online transportation services for motorbikes and cars using the FunoTrans application has a positive and significant effect; the price of other online transportation services for motorcycles and cars has a positive and significant effect; respondent's income has no significant effect; and user satisfaction have a significant effect on the demand for online transportation services in the FunoTrans application.